2016
DOI: 10.3748/wjg.v22.i34.7735
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and airway diseases

Abstract: Airway diseases are the most commonly described lung manifestations of inflammatory bowel disease (IBD). However, the similarities in disease pathogenesis and the sharing of important environmental risk factors and genetic susceptibility suggest that there is a complex interplay between IBD and airway diseases. Recent evidence of IBD occurrence among patients with airway diseases and the higher than estimated prevalence of subclinical airway injuries among IBD patients support the hypothesis of a two-way assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…Concurrently, the risk of new-onset IBD is found to be higher in populations with obstructive pulmonary diseases such as obstructive pulmonary disease (COPD), asthma, and bronchiectasis compared to the general population without these conditions [6,7,8]. This newly documented evidence of IBD incidence among patients with pulmonary diseases and the higher than the estimated prevalence of pulmonary conditions among IBD patients support the hypothesis of a two-way association [5].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Concurrently, the risk of new-onset IBD is found to be higher in populations with obstructive pulmonary diseases such as obstructive pulmonary disease (COPD), asthma, and bronchiectasis compared to the general population without these conditions [6,7,8]. This newly documented evidence of IBD incidence among patients with pulmonary diseases and the higher than the estimated prevalence of pulmonary conditions among IBD patients support the hypothesis of a two-way association [5].…”
Section: Introductionmentioning
confidence: 59%
“…Patients with IBD are at an elevated risk of autoimmune and inflammatory conditions [4]. Airway diseases are one of the most commonly studied manifestations of IBD [5]. Concurrently, the risk of new-onset IBD is found to be higher in populations with obstructive pulmonary diseases such as obstructive pulmonary disease (COPD), asthma, and bronchiectasis compared to the general population without these conditions [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…PFTs might be used as a noninvasive means of diagnosis to determine the activity of disease and might contribute to the early detection of latent pulmonary involvement [36]. On the other hand, there is a new growing evidence of an inter-relation between IBD and airway diseases that not only airway diseases occur as extra intestinal manifestations of IBD, but also there's relative risk increase of IBD occurrence among patients with pulmonary airway diseases as asthma, chronic obstructive pulmonary disease (COPD) and bronchiectasis, Future research should be carried out for further exploration of this tow-way association [33]. There is a retrospective cohort study conducted by Paul Brassard in 2014 to assess whether the incidences of Crohn's disease and ulcerative colitis are increased in patients with asthma and chronic obstructive pulmonary disease (COPD) compared to the general population during 2001-2006, they found that the incidences of both Crohn's disease and ulcerative colitis were markedly increased in asthma and COPD patients during 2001-2006 compared to the general population of Québec.…”
Section: Incidence Yearmentioning
confidence: 99%
“…Episcleritis [25] Scleritis [25] Uveitis Incidence of the pulmonary complication reported as relatively rare extra intestinal manifestation of Crohn's disease; 21% to 41% of patients with IBD patients had pulmonary complications and are more common in Crohn's disease (CD) than in ulcerative colitis (UC), 400 cases with CD has been recognized and reported in the literature with pulmonary involvement [32][33][34][35][36][37], it's occasionally possibly causing serious illness that needs pulmonary evaluation, a wide spectrum of lung manifestations , extending from subclinical changes without any symptoms, upper and lower airway diseases, parenchymal diseases of lung up to pleural involvement in addition to medication side effects. The most obvious complication is bronchial inflammation and suppuration with or without bronchiectasis.…”
Section: Incidence Yearmentioning
confidence: 99%
“…However, the similarities in disease pathogenesis and the sharing of important environmental risk factors and genetic susceptibility suggest that there is a complex interplay between IBD and airway diseases 85 .…”
mentioning
confidence: 99%